1994
DOI: 10.1002/art.1780370712
|View full text |Cite
|
Sign up to set email alerts
|

N‐Monomethyl arginine, an inhibitor of nitric oxide synthase, suppresses the development of adjuvant arthritis in rats

Abstract: Objective. To test the hypothesis that nitric oxide (NO) is involved in the pathophysiology of arthritis.Methods. Arthritis was induced in male Lewis rats by the injection of adjuvant into the base of the tail. The NO synthase (NOS) inhibitor, NG-monomethyl-Larginine (L-NMA), was administered daily by the oral route for 19 days. Paw swelling, plasma fibrinogen levels, and urinary NOJNO, levels were measured to assess the effect of L-NMA on the arthritic response and whole-body NO production, respectively. On d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
108
2
3

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(117 citation statements)
references
References 20 publications
4
108
2
3
Order By: Relevance
“…The second phase of AIA is the development of inflammatory arthritis, which is temporally associated with an increase in multiple cytokines (including interleukin-1 [IL-11, IL-2, IL-6, tumor necrosis factor a [TNFa], and interferon-y) (1,12), an increase in NO production (27)(28)(29)(30)(31), and a rise in circulating acute-phase reactants (lJ2). As a composite, these abnormalities are a hallmark of the intense systemic and local inflammatory response seen in AIA; however, the contribution of each component to disease progression is uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The second phase of AIA is the development of inflammatory arthritis, which is temporally associated with an increase in multiple cytokines (including interleukin-1 [IL-11, IL-2, IL-6, tumor necrosis factor a [TNFa], and interferon-y) (1,12), an increase in NO production (27)(28)(29)(30)(31), and a rise in circulating acute-phase reactants (lJ2). As a composite, these abnormalities are a hallmark of the intense systemic and local inflammatory response seen in AIA; however, the contribution of each component to disease progression is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reduced the severity of AIA (28,32,33) and of streptococcal cell wall-induced arthritis (26) in rats using N-methyl-L-arginine, a NOS inhibitor, which suggests a fundamental role for NO pathways in these experimental models (26,28). However, a recent evaluation of several iNOS inhibitors in AIA showed that aminoguanidine was able to suppress the level of urinary nitrate excretion during AIA without a reduction in arthritis severity (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the role of NO in arthritis is largely unknown. In contrast, NOS inhibitors were reported to suppress adjuvant and streptococcal cell wall-induced arthritis [15][16][17], yet had no effect on borrelial arthritis [18].…”
Section: Introductionmentioning
confidence: 99%